The Effects of a Pedal-less Bicycle Intervention on Stability Scores among Preschool Aged Children. Issue 2 (4th March 2021) - Shim, Andrew; Davis, William; Newman, David; Abbey, Bryce; Garafalo-Peterson, Jaime
Abstract: The purpose of this preliminary investigation was to determine if an intervention program using pedal-less bicycles could improve stability scores among preschool aged children. Currently, there has not been literature demonstrating if this intervention will improve balance scores. Twenty healthy children, aged three to five years old were recruited to determine if pedal-less bicycles would improve balance scores after four weeks. This study used a two group experimental/control repeated measures design analyzed with mixed-effects repeated measures analysis of variances to determine if Center of Pressure (CoP) and Limit of Stability (LoS) scores changed during the four weeks. Significant differences in mean performance were detected in the experimental group for LoS in the anterior plane (p = .012), in the left sagittal (p = 0.010), and in the right sagittal plane (p < 0.001), especially during week three and four. There was evidence of significant associations with pedal-less bicycle riding and mean stability scores in three to five year old children within four weeks of training.